Prevalence, population structure and burrow morphology of the kelp-boring amphipod Sunamphitoe roberta. Issue 2 (3rd April 2022) - Wilcox, MJ; Landschoff, J; Griffiths, CL
Abstract : The recently described amphipod Sunamphitoe roberta lives only on the kelp Ecklonia maxima, where it excavates slit-like burrows along the distal margins of thicker primary fronds. Oval chambers along the bases of these slits may represent feeding areas. As burrowing proceeds, the damage progressively erodes back the frond margins, giving them characteristic attenuated and irregular profiles, and probably impacting secondary frond survival and growth, and hence kelp productivity. A kelp forest in False Bay, South Africa, was surveyed to determine what proportion of kelp was infected as well as which individuals were selected as hosts. Forty kelp heads were also dissected to ascertain numbers of amphipods per host and their size composition, and to document details of burrow structure. Of 305 adult kelps inspected, 117 (38.4%) showed visible amphipod damage. Rate of infestation was not correlated with stipe length but was positively correlated with head circumference and negatively correlated with the proportion of secondary fronds remaining. The 40 kelp heads dissected contained 786 S. roberta specimens. These comprised 154 adults (>8 mm), including 33 ovigerous females, and 632 juveniles (<8 mm). The number of amphipods per host ranged from 1 to 112 (mean 19.7 [SD 25.1]). Size distribution was bimodal, and the largest individual measured 20 mm.